Psychological features of perception of artworks by people with different types of functional brain asymmetry - O. Kresan (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
The relevance of the study is conditioned by the increased attention of modern psychology to individual personality traits and its decreased focus on the normativity of an individual. In the process of individual development, the contemplation of art allows a person not only to broaden their own worldview, but also contributes to cultural enrichment. The purpose of the study was an empirical investigation of the features of perception of works of art by persons with different types of functional brain asymmetry. The study was conducted using the method of standardised interviews with the subjects of two groups: the main group – people who do not have professional knowledge of art (N = 43), and the control group – students studying art history and fine arts as professional disciplines, and familiar with the rules for constructing composition in a picture (N = 30). The results were analysed using statistical criteria: the Kolmogorov-Smirnov test and the Fisher angular transformation criterion φ*. As a result of the empirical study, there were no statistically reliable patterns in the perception of works of art in the general group, but significant differences were found in the features of perception of movement and its speed in works of art by persons with different types of functional/interhemispheric brain asymmetry, which indicates a nonlinear nature of perception, and the influence of cognitive phenotypes on the perception of works of art. The perception of artworks is an individual cognitive process that may differ between the author and the recipient of artistic creativity, and the author’s intention may be misunderstood by the audience if the features of individual perception of a work of art, and the laterality of the personality, are not considered. The practical significance of the study lies in the possibility of applying its results in the process of professional training of students of art specialities, considering the specific features of the laterality of art recipients